Optimising the zebrafish Cre/Lox toolbox. Codon improved iCre, new gateway tools, Cre protein and guidelines - Tromp, Alisha; Wang, Haitao; Hall, Thomas E.; Mowry, Bryan; Giacomotto, Jean (Frontiers in Physiology, 2023)
We recently introduced the Cre/Lox technology in our laboratory for both transient (mRNA injections) and stable/transgenic experiments. We experienced significant issues such as silencing, mosaicism, and partial recombination using both approaches. Reviewing the literature gave us the impression that these issues are common among the zebrafish community using the Cre/Lox system. While some researchers took advantage of these problems for specific applications, such as cell and lineage tracing using the Zebrabow construct, we tried here to improve the efficiency and reliability of this system by constituting and testing a new set of tools for zebrafish genetics. First, we implemented a codon-improved Cre version (iCre) designed for rodent studies to counteract some of the aforementioned problems. This eukaryotic-like iCre version was engineered to (i) reduce silencing, (ii) increase mRNA stability, (iii) enhance translational efficiency, and (iv) improve nuclear translocation. Second, we established a new set of tol2-kit compatible vectors to facilitate the generation of either iCre-mRNA or iCre-transgenes for transient and transgenic experiments, respectively. We then validated the use of this material and are providing tips for users. Interestingly, during the validation steps, we found that maternal iCRE-mRNA and/or protein deposition from female transgenics systematically led to complete/homogeneous conversion of all tested Loxresponder-transgenes, as opposed to some residual unperfect conversion when using malesdrivers or mRNA injections. Considering that we did not find any evidence of Cre-protein soaking and injections in the literature as it is usually conducted with cells, we tested these approaches. While soaking of cell-permeant CRE-protein did not lead to any detectable Loxconversion, 1ng to 10ng protein injections led to robust and homogeneous Lox-recombination, suggesting that the use of protein could be a robust option for exogenous delivery. This approach may be particularly useful to manipulate housekeeping genes involved in development, sex determination and reproduction which are difficult to investigate with traditional knockout approaches. All in all, we are providing here a new set of tools that should be useful in the field.